Wideband Circularly Polarized Spidron Fractal Slot Antenna with an Embedded Patch - Amir Altaf; Youngoo Yang; Kang-Yoon Lee; Keum Cheol Hwang (International Journal of Antennas and Propagation)
In this communication, a wideband circularly polarized (CP) Spidron fractal microstrip antenna is proposed based on the concept of embedded structures. The proposed antenna is excited by a tapered microstrip feedline. A wide 3 dB axial ratio (AR) bandwidth of 28.81% (3.09–4.13 GHz) is obtained by merging the CP bands of the Spidron fractal slot and patch antennas. In addition, a measured −10 dB reflection bandwidth of 47.25% (2.57–4.16 GHz) is reported. The measured results are in reasonable concurrence with the simulated results. The measured gain varies between 2.12 dBic and 3.56 dBic within the AR bandwidth.